2020
DOI: 10.1098/rspb.2020.0877
|View full text |Cite
|
Sign up to set email alerts
|

A scientist like me: demographic analysis of biology textbooks reveals both progress and long-term lags

Abstract: Textbooks shape teaching and learning in introductory biology and highlight scientists as potential role models who are responsible for significant discoveries. We explore a potential demographic mismatch between the scientists featured in textbooks and the students who use textbooks to learn core concepts in biology. We conducted a demographic analysis by extracting hundreds of human names from common biology textbooks and assessing the binary gender and race of featured scientists. We found that the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…Additionally, many science instructors hold the assumption that STEM fields are somehow "unbiased" and immune to societal injustices (Saini, 2020;Smith & Scharmann, 1999;Wheeler et al, 2019) Smedley & Smedley, 2005;Vakil & Ayers, 2019). Disparities start early, as a recent study found introductory biology textbooks were more likely to highlight men scientists, and none of the books analyzed highlighted a Black woman scientist (Wood et al, 2020). These biases impact students' first view of the field and can shape the ideas of who belongs in science; these disparities are something instructors can actively address in their individual syllabi and curriculum.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Additionally, many science instructors hold the assumption that STEM fields are somehow "unbiased" and immune to societal injustices (Saini, 2020;Smith & Scharmann, 1999;Wheeler et al, 2019) Smedley & Smedley, 2005;Vakil & Ayers, 2019). Disparities start early, as a recent study found introductory biology textbooks were more likely to highlight men scientists, and none of the books analyzed highlighted a Black woman scientist (Wood et al, 2020). These biases impact students' first view of the field and can shape the ideas of who belongs in science; these disparities are something instructors can actively address in their individual syllabi and curriculum.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…This new paper category has been quite successful, with 30 submissions—and five papers published—to date since late 2019, including several (e.g. [ 14 ]) receiving quite a bit of positive international media attention.…”
Section: Challenges: Some Solutions But Some Continuementioning
confidence: 99%
“…A constructive strategy to guide all of your students to feel and think like scientists is to cultivate an inclusive atmosphere inside and outside of the classroom (Dewsbury, 2020; Dewsbury & Brame, 2019). Some simple practices include facilitating balanced groups, learning names, using pronouns, supportive messaging in your syllabus, and increasing representation and relevance in your teaching materials (Wood et al., 2020). Materials should also be designed with accessibility in mind.…”
Section: Building Inclusivity In Teaching and Research Environmentsmentioning
confidence: 99%